REDUKSI MASALAH CAUCHY ABSTRAK DEGENERATE KE MASALAH CAUCHY ABSTRAK NONDEGENERATE - Haryanto, Susilo (MATEMATIKA, 2005)
ï»¿ï»¿ï»¿In this article, we investigate how to reduce an abstract degenerate Cauchy problem to an abstract nondegenerate Cauchy problems. This problem is discussed in the Hilbert space which can be writen as an orthogonal direct sum of Ker M and . Under certain assumptions, abstract degenerate Cauchy problems can be reduced to abstract nondegenerate Cauchy problems which is easier to solve. If we have a solution of abstract nondegenerate Cauchy problem, then using certain transformation we can find the solution of abstract degenerate Cauchy problems. Â